Dynamic compressive behavior of fiber reinforced Al/PTFE active materials - Enling Tang; Sheng Li; Chuang Chen; Yafei Han (Journal of Materials Research and Technology, 2020)
To investigate the dynamic compressive behavior of zirconium filaments/aluminum/polytetrafluoroethylene (mass fraction of Zr fiber/Al/PTFE of 3%/23.5%/73.5%) active materials, traditional formula Al/PTFE active materials (Al/PTFE mass fraction of 26.5%/73.5%) and Al/Zr/PTFE active materials were prepared by cold pressing sintering process. The microscopic morphology and impact reaction behavior of the material by scanning electron microscopy (SEM) and high-speed camera are observed. The dynamic compressive experiments of the two materials are carried out by using separate Hopkinson bar (SHPB) test system. The results show that the Al/PTFE by adding active metal zirconium (Zr) filaments can improve the dynamic compressive properties of conventionally Al/PTFE. The failure strength of active material is increased from 32 MPa to 110 MPa comparing with conventionally Al/PTFE active materials, and the increase is about 243.75%. When the strain rate is 2500–4000 s−1, Al/Zr/PTFE specimens exhibit the same elastic–plastic mechanical behavior as conventionally Al/PTFE specimens. The behavior of the two specimens can also be divided into three stages: compressive deformation, crack generation and hot spot initiation (there are microscopic holes around Zr fibers, and the collapse and expansion of holes is the main reason for the formation of hot spots).